Aesthetic (dis)education in Weapon is a part of my body: Body and politics in discourse (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article presents reflections triggered by the show Weapon is a part of my body, a co-production between Brazil, Israel and the United Kingdom, with the performance of the Brazilian Pedro Granato and the Israeli Ruthie Osterman, taking as a guiding principle the set of potentialities that the work offers to think about what we call, in this essay, as aesthetic (dis)education and the intersections with the debates about body and politics in the contemporary scene. The theoretical-methodological framework has its framework varnished by the Dialogical Analysis of Discourse, of which we chose as the base text the essay The problem of content, material and form in literary creation, written by Bakhtin in 1934, in which the author proposes a discussion about general aesthetics.
Keywords: Aesthetic (dis)education; Body; Politics; Discourse